A psicanálise entre a higiene mental e a escola nova na obra de Arthur Ramos: contribuições à história da educação no Brasil - Mercadante, Jefferson [UNESP] (2015)
The present work is a theoretical, bibliographic and critical analysis on the psychoanalytical production of Arthur Ramos in the scope of Primary Education, as well as of its relations with Mental Hygiene and the New School movements. To do so, the following books of Ramos were studied: Educação e Psychanalyse (1934) and A Criança Problema (1939). Our hypothesis was that Arthur Ramos's theory contributed to the organization of bourgeois society and its progress, masking the political and social relations of capitalist modernity. Our objective was to deepen the ethical and political sense of the relationship between the New School and the Mental Hygiene movement from a critical and detailed analysis of such works and the medical records of children of experimental schools, conducted by Serviço de Ortofrenia e Higiene Mental, headed by Arthur Ramos between 1934 and 1939. We utilized critical theory as our main approach method, represented by the philosopher Theodor Wiesengrund Adorno. To do so, we considered the social, cultural and economic dimension of society as fundamental for Ramos’ speech. In a first moment a critical review of the literature about hygienist and the New School in Brazil was made, with particular attention to the definition concepts related in its relations. Secondly, we intended to understand how the diffusion and implantations of psychoanalytical theory in relation with the Primary Education in the Freudian and post-Freudian eras. Finally, we critically analyzed Arthur Ramos’ production and career in the Serviço de Ortofrenia e Higiene Mental of Rio de Janeiro in the decade of 1930 to comprehend his place among the concepts of Mental Hygiene, New School and Psychoanalysis. We conclude that the intellectual Arthur Ramos stood in a discursive field which tried to fit the population to a project in Brazil who identified progress and intense social control, a project of civilization and barbarism. We present ...